Structure, Activity Regulation, and Role of the Mitochondrial Calcium Uniporter in Health and Disease - Mammucari, Cristina; Gherardi, Gaia; Rizzuto, Rosario (Frontiers in Oncology, 2017)
Mitochondrial Ca2+ uptake plays a pivotal role both in cell energy balance and in the determination of cell fate. Studies on the role of mitochondrial Ca2+ signaling in pathophysiology have been favoured by the identification of the genes encoding the Mitochondrial Calcium Uniporter (MCU) and its regulatory subunits. Thus, research carried on in the last years on one hand has determined the structure of the MCU complex and its regulation, on the other has uncovered the consequences of dysregulated mitochondrial Ca2+ signaling in cell and tissue homeostasis. Whether mitochondrial Ca2+ uptake can be exploited as a weapon to counteract cancer progression is debated. In this review we summarize recent research on the molecular structure of the MCU, the regulatory mechanisms that control its activity, and its relevance in pathophysiology, focusing in particular on its role in cancer progression.